2020
DOI: 10.1017/lsi.2019.70
|View full text |Cite
|
Sign up to set email alerts
|

From Punishment to Control: Assessing Juvenile Diversion in China

Abstract: China’s juvenile justice system has grown and changed substantially since the 1980s. While considerable research focuses on institutional treatment of juvenile delinquents, little attention has been paid to the diversion processes and measures that allow troubled juveniles to be directed away from the formal justice system. Through a comparison with juvenile justice in the United States, this article aims to investigate the development of the juvenile diversion framework in China. We argue that despite their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Study has found that almost all of juvenile sexual offenders grew up in a dysfunctional family, and this factor has proven to be one of the most common issues in other types of crimes as well (Vieth, 2022). It's also suggested by other research that restorative justice in general, especially the one that revolves around risk-based management and correction through community-level interventions, can help prevent further involvement in crimes among juvenile offenders (Li & Su, 2020).…”
Section: Impact-focused Approach To Implement Restorative Justice App...mentioning
confidence: 99%
“…Study has found that almost all of juvenile sexual offenders grew up in a dysfunctional family, and this factor has proven to be one of the most common issues in other types of crimes as well (Vieth, 2022). It's also suggested by other research that restorative justice in general, especially the one that revolves around risk-based management and correction through community-level interventions, can help prevent further involvement in crimes among juvenile offenders (Li & Su, 2020).…”
Section: Impact-focused Approach To Implement Restorative Justice App...mentioning
confidence: 99%
“…Criminal Justice Officials can disengage from the formal process of perpetrators for a number of reasons. Diversion usually occurs when it is believed that it will be better for both the perpetrator and the community if the case is diverted from the formal process (Li & Su, 2020). This alternative punishment is one solution so that transgender inmates get clear legal certainty and can also obtain their rights as prisoners in prison.…”
Section: The Ideal Criminal Modification Concept For Transgender Conv...mentioning
confidence: 99%